Real-Time Demand Response Program Implementation Using Curtailment Service Provider - Abrishambaf, Omid (2021)
Nowadays, electricity network operators obligated to utilize the new concepts of power system, such as demand response program, due to peak shaving or reducing the power congestion in the peak periods. These types of management programs have a minimum capacity level for the consumers who tend to participate. This makes small and medium scale consumer incapable to participate in these programs. Therefore, a third party entity, such as a Curtailment Service Provider, can be a solution for this barrier since it is a bridge between the demand side and grid side. This paper provides a real-time simulation of a curtailment service provider that utilize realtime demand response programs for small and medium consumers and prosumers. The case study of the paper represents a network with 220 consumers and 68 distributed generations, which aims at the behavior of two small and medium scale prosumers during a real-time demand response program.